Non-degreed youth’s employability, career adaptability, and psychological capital at an educational institution - Van Vuuren, J.; Oosthuizen, R. M.; Steyn, L. (South African Journal of Higher Education, 2024)
Technological developments and the Fourth Industrial Revolution (4IR) make employability more important than employment. The youth are forced to adopt a protean career and constantly adjust their skills, knowledge and behaviour to maintain their employability and skills relevance. Psychosocial career resources assist them in coping with career challenges and setbacks through career adaptability and remaining employable. The study investigated the relationship between employability, career adaptability, and psychological capital amongst non-degreed youth at an educational institution. To cope with contemporary work environment demands, the youth must be equipped with the competencies and know-how to flex their careers appropriately. At the time of the study, no research had examined the relationship between employability, career adaptability and psychological capital. The study used a cross-sectional, quantitative, non-experimental research approach to explore the interrelatedness of the variables. The results demonstrated a strong, positive and significant relationship between employability and career adaptability; employability and psychological capital; and career adaptability and psychological capital. The relationship between employability and career adaptability was more conspicuous than the relationship between employability and psychological capital. Cultivating employability attributes, career adaptability, and psychological support may strengthen the youths’ self-perceived employability and improve how they adjust their careers according to work environment demands. The study explains how employability, career adaptability, and psychological capital relate. Its findings can be used to advance youth employability.